Optimizing the utilization of biochar from waste: an energy–water–food nexus assessment approach considering water treatment and soil application scenarios - Obar, Farah; Alherbawi, Mohammad; Mckay, Gordon; Al-Ansari, Tareq (Frontiers in Environmental Science, 2023)
As a result of the rapid population increase and depletion of natural resources, namely energy and water, approximately 200 million people are expected to face hunger by 2030. Going forward, the sustainability of energy, water and food (EWF) resources can be enhanced by considering a nexus approach, which supports effective resource management through identifying synergies and trade-offs.Furthermore, the regeneration of biomass into value-added products, such as biochar (BC) can reduce cross-sectoral environmental impacts and support the EWF nexus. Considering, this research investigates the optimum options for utilizing BC within the context of EWF nexus for both wastewater treatment and soil applications, whilst considering the optimal blending ratio of various biomass (camel manure, date pits, sewage sludge and coffee waste) for both single-end use and multi-end use stages, to fulfill various objectives within defined scenarios based on maximum savings in energy, water, cost and emissions. The single-end use stage considered using BC for wastewater treatment (WWT) and as a soil amendment (SA) individually, where 18 optimal solutions were collected for this stage. The optimization of the multi-end use stage resulted in 70 optimal solutions where BC was applied for both WWT and SA. The solutions that leant towards SA application suggested that BC should consist of 97 -99% of date pits with relatively smaller proportions of the other biomass. Whilst the other solutions that leant towards WWT pathway suggested that the optimum biomass mix should consist of relatively equal proportions of camel manure, sewage sludge and coffee waste of 29 -33% and smaller amounts of date pits around 2 -5%.